The p97‐Nploc4 ATPase complex plays a role in muscle atrophy during cancer and amyotrophic lateral sclerosis. Issue 4 (25th May 2022) - Re Cecconi, Andrea David; Barone, Mara; Gaspari, Simona; Tortarolo, Massimo; Bendotti, Caterina; Porcu, Luca; Terribile, Giulia; Piccirillo, Rosanna
Abstract: Background: The p97 complex participates in the degradation of muscle proteins during atrophy upon fasting or denervation interacting with different protein adaptors. We investigated whether and how it might also be involved in muscle wasting in cancer, where loss of appetite occurs, or amyotrophic lateral sclerosis (ALS), where motoneuron death causes muscle denervation and fatal paralysis. Methods: As cancer cachexia models, we used mice bearing colon adenocarcinoma C26, human renal carcinoma RXF393, or Lewis lung carcinoma, with breast cancer 4T1‐injected mice as controls. As ALS models, we employed 129/SvHsd mice carrying the mutation G93A in human SOD1. The expression of p97 and its adaptors was analysed in their muscles by quantitative real‐time polymerase chain reaction (qPCR) and western blot. We electroporated plasmids into muscles or treated mice with disulfiram (DSF) to test the effects of inhibiting p97 and nuclear protein localization protein 4 (Nploc4), one of its adaptors, on atrophy. Results: The mRNA levels of p97 were induced by 1.5‐fold to 2‐fold in tibialis anterior (TA) of all the cachectic models but not in the non‐cachectic 4T1 tumour‐bearing mice ( P ≤ 0.05). Similarly, p97 was high both in mRNA and protein in TA from 17‐week‐old SOD1 G93A mice ( P ≤ 0.01). Electroporation of a shRNA for murine p97 into mouse muscle reduced the fibre atrophy caused by C26 ( P = 0.0003) or ALS ( P ≤ 0.01). When we interrogated a microarray, we had previously generated for the expression of p97 adaptors, we found Derl1, Herpud1, Nploc4, Rnf31, and Hsp90ab1 induced in cachectic TA from C26‐mice (Fold change > 1.2, adjusted P ≤ 0.05). By qPCR, we validated their inductions in TA of cachectic and ALS models and selected Nploc4 as the one also induced at the protein level by 1.5‐fold ( P ≤ 0.01). Electroporation of a CRISPR/Cas9 vector against Nploc4 into muscle reduced the fibre atrophy caused by C26 ( P = 0.01) or ALS ( P ≤ 0.0001). Because DSF uncouples p97 from Nploc4, we treated atrophying myotubes with DSF, and found accumulated mono and polyubiquitinated proteins and reduced degradation of long‐lived proteins by 35% ( P ≤ 0.0001), including actin ( P ≤ 0.05). DSF halves Nploc4 in the soluble muscle fraction ( P ≤ 0.001) and given to C26‐bearing mice limited the body and muscle weight loss ( P ≤ 0.05), with no effect on tumour growth. Conclusions: Overall, cancer cachexia and ALS seem to display similar mechanisms of muscle wasting at least at the catabolic level. The p97‐Nploc4 complex appears to have a crucial role in muscle atrophy during these disorders and disrupting this complex might serve as a novel drug strategy.